Meningkatkan Hasil Belajar Siswa Melalui Penerapan Model Pembelajaran Mind Mapping - Sitti Nur Halizah; Syamsurijal Basri (Universitas Negeri Makassar, 2024)
The purpose of this research is to know the learning process and student outcomes of the fourth grade students of UPT SD Negeri Inpres Karawa, Pinrang Regency by implementation of cooperative learning model type mind mapping in learning sources of energy. This research uses qualitative research methods with classroom action research. The data collection techniques used were observation, tests and documentation. The procedure for implementing the action consists of four stages, namely planning, implementing, observing and reflecting. The research was conducted in three cycles involving teachers and students. The results obtained indicate that each cycles showed a sginificant improvement. The implementation of cooperative learning model type mind mapping can improve the process and student achievement in learning sources of energy grade IV UPT SD Negeri Inpres Karawa, Pinrang Regency.